Building blocks for better biorepositories in Africa - Talishiea Croxton; Emmanuel Jonathan; Kareemah Suleiman; Olasinbo Balogun; Petronilla J. Ozumba; Sharley M. Aloyo; Gideon Nsubuga; Rogers E. Kamulegeya; Lwanga Newton; John Mukisa; Mukthar Kader; Vuyo Damaneite; et al. (Genome Medicine)
Abstract Background Biorepositories archive and distribute well-characterized biospecimens for research to support the development of medical diagnostics and therapeutics. Knowledge of biobanking and associated practices is incomplete in low- and middle-income countries where disease burden is disproportionately high. In 2011, the African Society of Human Genetics (AfSHG), the National Institutes of Health (NIH), and the Wellcome Trust founded the Human Heredity and Health in Africa (H3Africa) consortium to promote genomic research in Africa and established a network of three biorepositories regionally located in East, West, and Southern Africa to support biomedical research. This manuscript describes the processes established by H3Africa biorepositories to prepare research sites to collect high-quality biospecimens for deposit at H3Africa biorepositories. Methods The biorepositories harmonized practices between the biorepositories and the research sites. The biorepositories developed guidelines to establish best practices and define biospecimen requirements; standard operating procedures (SOPs) for common processes such as biospecimen collection, processing, storage, transportation, and documentation as references; requirements for minimal associated datasets and formats; and a template material transfer agreements (MTA) to govern biospecimen exchange. The biorepositories also trained and mentored collection sites in relevant biobanking processes and procedures and verified biospecimen deposit processes. Throughout these procedures, the biorepositories followed ethical and legal requirements. Results The 20 research projects deposited 107,982 biospecimens (76% DNA, 81,067), in accordance with the ethical and legal requirements and established best practices. The biorepositories developed and customized resources and human capacity building to support the projects. [The biorepositories developed 34 guidelines, SOPs, and documents; trained 176 clinicians and scientists in over 30 topics; sensitized ethical bodies; established MTAs and reviewed consent forms for all projects; attained import permits; and evaluated pilot exercises and provided feedback. Conclusions Biobanking in low- and middle-income countries by local skilled staff is critical to advance biobanking and genomic research and requires human capacity and resources for global partnerships. Biorepositories can help build human capacity and resources to support biobanking by partnering with researchers. Partnerships can be structured and customized to incorporate document development, ethics, training, mentorship, and pilots to prepare sites to collect, process, store, and transport biospecimens of high quality for future research.